Assessing the Socio-Economic Impacts of Solar Home Systems on Chingad, Surkhet - Oli, Lok Bahadur; Woli, Lokendra (International Research Journal of MMC, 2024)
This study assesses the multifaceted socio-economic impacts of Solar Home Systems (SHS) on the remote community of Chingad, Surkhet. Employing a comprehensive research framework, we investigate the extent to which the adoption of SHS has influenced the livelihoods, economic activities, and social dynamics within the community. Through a combination of quantitative and qualitative methodologies, we analyzed the economic benefits, social empowerment, and environmental sustainability associated with the integration of solar energy. The limitations of the study included its focus on Chindgad-5, Surkhet. This research employed a descriptive-analytic approach within an exploratory research design. In the study area, a total of 386 households were included, with 188 utilizing solar energy in December 2023 AD from field observation. The research focused on a subset of 36 purposely selected solar home system users. Energy consumption patterns varied among ethnic groups and social classes, and universal electricity access was not observed in the study area. The study integrated both descriptive and exploratory elements to comprehensively address its objectives, utilizing a combination of primary and secondary data. For policymakers, development professionals, and other stakeholders engaged in sustainable energy projects in similar circumstances, the findings offer insightful information about the complex relationships that are present between solar technology and the local socioeconomic fabric. The study provides valuable insights for policymakers, energy planners, and development organizations working towards sustainable and inclusive energy solutions in rural Nepal. The successful integration of SHS not only addresses energy needs but also contributes to economic development and improved living conditions in off-grid communities.